The Study Of Communicative Intellectuality Place/Role In The Expansion Of General Domain From The Perspective Of Modern Theorists Of Communication - Foroughi, Maryam; Majidy, Nassim (The Turkish Online Journal of Design Art and Communication, 2016)
The main idea of the lack of a master and general plan concerning the status of rationality and its evolution was shaped as a communicative rationality in communication science. The communicative place rationality in the public domain from the perspective of modernity theorists is the basic question in this field. Procedure of the research is qualitative research method with qualitative analysis of Max Weber. The first step of the research is an overview of research topic, objectives, research methods and Statistical Society. The next step is a deep study in the evolution of history of ancient Greece, during the development of Christianity and the explanation of votes in the Christian era, the Enlightenment and the intellectual revolution. Also, entries on topics such as the definition of modernism and modernity that define the modern scientific achievements and the consequences of modernity and its crisis on modernity and rationality is studied in this research. Finally, the communicative rationality and rationalization of the development and differentiation and achieve communicative rationality is deliberated. This section is fed mostly by Habermas's ideas and thoughts.
Keywords: Renaissance; Communicative Intellectuality; Domain; Perspective; Habermas's Ideas